Porous Supramolecular Crystalline Materials for Photocatalysis - Gong, Yun‐Nan; Zhong, Di‐Chang; Lu, Tong‐Bu (Angewandte Chemie International Edition, 2025)
Porous supramolecular crystalline materials (PSCMs), such as hydrogen‐bonded organic frameworks (HOFs), π frameworks, can be defined as a type of porous supramolecular assemblies stabilized by hydrogen‐bonding, π‐π stacking and other non‐covalent interactions. Benefiting from the unique features of mild synthesis conditions, well‐defined and synthetically tailorable structures, easy healing and regeneration, PSCMs have garnered widespread interest in research fields including molecular recognition, sensor, gas storage and separation. Moreover, they have emerged as promising photocatalysts because these PSCMs could be readily endowed with optical function, and the hydrogen‐bonding and π‐π stacking can offer channels for electron transfer to boost the photocatalytic activity. However, the research on PSCMs for photocatalysis is still at an early stage, and a review on this topic would help to promote the development of supramolecular chemistry. In this Minireview, we first introduce the synthesis methods for PSCMs, and then highlight their advantages in photocatalysis. Subsequently, we summarize the applications of PSCMs in photocatalysis including CO2 reduction, H2 evolution, H2O2 production, organic transformation and pollutant degradation, and we put particular emphasis on delineating the structure‐performance relationship. At the end, we discuss the challenges and perspectives in developing high‐performance PSCM‐based photocatalysts. Porous supramolecular crystalline materials (PSCMs) are a type of porous supramolecular assemblies stabilized by hydrogen‐bonding, π‐π stacking and other non‐covalent interactions, which have shown great potential in photocatalysis by virtue of their unique features of well‐defined and synthetically tailorable structures, mild synthesis conditions, easy healing and regeneration. In this Minireview, we summarize the syntheses, structural features and photocatalytic applications for PSCMs, including CO2 reduction, H2 evolution, H2O2 production, organic transformation and pollutant degradation. The challenges and opportunities for developing high‐performance PSCMs‐based photocatalysts are also put forward.